Designing a Short Film to Integrate Literacy into Daily Life: A Case Study of Library Café “The Room 19” - Alghonyu, Dhara; Soewardikoen, Didit Widiatmoko; Azhar, Hanif; Nurhadiansyah, Mahendra (Gorga : Jurnal Seni Rupa, 2025)
Literacy is a fundamental prerequisite for human comprehension. While Bandung boasts a diverse array of cafes that incorporate unique concepts such as movie, music, or nature themes, the presence of library-themed cafes remains a minority. Consequently, strategically incorporating the library cafe trend into contemporary life, encompassing aspects like lifestyle, presents a compelling strategy to promote literacy. By presenting the library concept within a welcoming and aesthetically pleasing cafe ambiance, this research employs a qualitative approach grounded in design thinking. Data collection involves questionnaires, interviews, and observations. Literacy is an indispensable aspect of daily life. One effective approach to enhancing literacy is through the design of short films that integrate literacy into the fabric of one’s lifestyle. By portraying literacy as a fashionable and engaging activity, short films can inspire college students and learners to incorporate reading into their daily routines, thereby reinforcing literacy culture.